The Impact of Affective Commitment in Employees Life Satisfaction (Global Journal of Management and Business Research, 2014)
A commitment refers to attachment and loyalty. An affective commitment is an employee's emotional attachment to, identification with and involvement in an organization. It influence personal characteristics, structural characteristics, and work experiences. The purpose of it is study is to analyse the role of affective commitment in employee's life satisfaction. Life satisfaction is the embodiment of a global judgment about one's life taken as a whole. It is positive evaluation of the condition of one's life, judgment. In this study sample includes 200 employees of NTPC of India from Sonbhadra District. The sample consisted of managerial employees who volunteered to participate in the study.The data has been analysing by descriptive analysis, correlation, linear regression, and ANOVA. The results were found that organizational affective commitment is highly significantly related with life satisfaction among managerial employees.
Keywords: affective commitment; life satisfaction